Analysis of Cystic Fibrosis in Federation of Bosnia and Herzegovina - Selimovic, Amina (Med Arch, 2015)
AIM: The aim of this study is to present the first total number of tested children in the Federation of Bosnia and Herzegovina and the number of children with positive sweat test. During the study we determined the number of ill children, the median age of children with cystic fibrosis, date of initial diagnosis, an average amount of chloride in the sweat. MATERIAL AND METHODS: The study was a retrospective, conducted at the Department of Pulmonology Pediatric Clinic of University Clinical Center of Sarajevo. RESULTS: In the period from March 2003 to December 2014, we have tested 625 children. 351 child were from Sarajevo Canton and 272 children from other cantons. Female children were more affected then male children, in the ratio of 1: 1,105. An average age of female children was 4.19±4.26 years, and the male 2.15±3.11 years. The median concentration of chloride in the sweat measured by sweat test was for male children 103.05±21.29 mmol/L, and for the female children 96.05±28.85 mmol/L. CONCLUSION: Most of children in Federation of Bosnia and Herzegovina have ∆F508 gene mutation. In the post-war period we started to use a sweat test. Male children tend to live longer than female children with CF.